Professores e parâmetros curriculares nacionais (PCN): Como está essa relação? - Nunes, Flaviana Gasparotti [UNESP] (My University, 2012)
The National Curricular Parameters (PCN) for primary school were introduced in 1998 within other deep educational changes promoted by the Brazilian State. In the field of Geography there have been heated discussions about the propositions put in this document as far as failures and gaps from a theoretical, methodological and didactical-pedagogical points of view are concerned. While some authors argue about its authoritarian character, others support its propositons stating that there is the need for a national curricular orientation. However, the PCN are now a reference for the teaching of Geography in Brazil subsidizing school plannings and assessment system. Hence, the need for a reflection on the effective connetion between teachers and the PCN is verified, i.e., the PCN consequences in the school teaching practice must be taken into consideration. In this text, we intend to work on some questions which might contribute to that.
Teachers and the national curricular parameters (PCN): What sort of connection is it?
Keywords: Curricular propositions; Geography; PCN; Teacher; Teaching